2019
DOI: 10.1002/2050-7038.12151
|View full text |Cite
|
Sign up to set email alerts
|

Variable step size PO MPPT algorithm using model reference adaptive control for optimal power extraction

Abstract: Summary To eliminate problems of traditional perturb and observe (TPO) maximum power point tracking (MPPT) relying on large scale variable speed wind energy conversion system (VS‐WECS), this paper suggests a variable step size perturb and observe (VS‐PO) MPPT algorithm. The VS‐PO technique is performed to split the power‐speed (P‐ω) curve with four segments every with a particular step size. A large step size is chosen for the two segments distant from the MPP. Otherwise, a smaller step size can be implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Based on the previous literature study, the comparative analysis of fuzzy and P&O PWM techniques have been carried out and it is found that P&O has maximum power(1300W) extraction than a fuzzy based system which extracts 1200W (Liu and Wang 2011;Ali et al 2020;Wu, Li, and Li 2017). A detailed theoretical (97.9%) and experimental comparison of the two P&O implementation techniques on basis of system stability the experimental P&O gives better performance (99%) for pumping applications (Elgendy, Zahawi, and Atkinson 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previous literature study, the comparative analysis of fuzzy and P&O PWM techniques have been carried out and it is found that P&O has maximum power(1300W) extraction than a fuzzy based system which extracts 1200W (Liu and Wang 2011;Ali et al 2020;Wu, Li, and Li 2017). A detailed theoretical (97.9%) and experimental comparison of the two P&O implementation techniques on basis of system stability the experimental P&O gives better performance (99%) for pumping applications (Elgendy, Zahawi, and Atkinson 2012).…”
Section: Discussionmentioning
confidence: 99%
“…PO algorithm is the conventional control strategy which is used to regulate the turbine speed to optimise the power. The PO technique is predicated on shifting the wind speed by a step-size and monitoring the modification within the extracted power until the slope of (P − ω) curve becomes zero (Ali et al 2020). The block diagram of PO algorithm based wind turbine control is shown in Fig.…”
Section: Tip Speed Ratio Methodsmentioning
confidence: 99%
“…Each RES controller contains an algorithm that is specific to that type of source. The PV controller controls the PV source using any MPPT strategy already known 22‐25 . The wind farm controller controls the wind turbines using the proportional repartition of the powers 17 or can use any other algorithms available in the literature 26‐29 .…”
Section: Active and Reactive Power Management Principalmentioning
confidence: 99%